A Bank Failure Prediction Model for Zimbabwe: A Corporate Governance Perspective - Chokuda, Tinevimbo Santu; Nkomazana, Njabulo; Mawanza, Wilford (Journal of Economics and Behavioral Studies, 2017)
The primary objective of this study was to come up with a bank failure prediction model for Zimbabwe. The research sample comprised five failed commercial banks that were operational in 2003 as well as five non-failed commercial banks that were operational during that same period. The model developed in this research was applied to each of these banks and a failure classification awarded. Out of a sample of ten banks, the model misclassified one bank as failed instead of non-failed and this signified a strong predictive power. Results revealed a distinct pattern of owner managed banks being predicted to fail while those banks run by professional managers, divorced from ownership, were getting high passes, a sign of stability. Some owner managed entities were predicted as non-failing and this was interpreted as emanating from a strong presence of institutional and other outside shareholders with a significant shareholding in the banks and thus eliminating shareholder concentration. The findings from the research showed that owner managers were more likely to commit corporate governance abuses than professional managers. It was concluded that corporate governance factors significantly contributed to the bank failures experienced in Zimbabwe between 2003 and 2004. As a result, banks need to focus more on corporate governance factors to avoid failures in the future.